Pearls for the middle fossa approach in acoustic neuroma surgery. Issue 5 (October 2018) - Peng, Kevin A.; Lekovic, Gregory P.; Wilkinson, Eric P.
Abstract : Purpose of review: To discuss the use of the middle fossa craniotomy for resection of vestibular schwannomas; to present pearls of and modifications to the approach. Recent findings: The middle fossa craniotomy allows for hearing preservation in the resection of intracanalicular vestibular schwannomas. Over recent years, the approach has been modified to address larger tumors with a limited cerebellopontine angle component. Positive identification of the superior semicircular canal allows for rapid exposure of the internal auditory canal (IAC). Removal of cerebrospinal fluid from the posterior fossa during exposure of the IAC allows for removal of the middle fossa retractor; reinforced silicone sheeting is used to protect the middle fossa dura during further drilling. The use of the endoscope has allowed for more complete dissection at the fundus of the IAC, including tumors lateral to the transverse crest. Summary: Technical modifications to the middle fossa craniotomy have allowed for a shorter duration of temporal lobe retraction intraoperatively and more complete resection of tumors with fundal involvement.